Foreign language learning as a factor of the inophone’s sociocultural adaptation - Качинський, О. С. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2019)
The article describes the features of the inophones’ sociocultural adaptation. One of the factors of the foreigner’s sociocultural adaptation – mastering the Ukrainian (Russian) language has been considered. The forms of work with foreign students to be helpful in their successful sociocultural adaptation have been proposed. The activity of the teacher is to manage the organization of active knowledge of the realities by the foreigners. It is also worth attracting foreigners to certain educational activities, excursions; organizing the concert programs both as observers and participants; arranging visits to various events where you can communicate with native Ukrainian (Russian) speakers. As a result of linguistic education, the students can and should be formed: readiness to comprehend a socio-cultural portrait of the country, the target language, and understanding of the native speakers; ethnic, racial and social tolerance, language tact and socio-cultural politeness; propensities to find non-violent ways to resolve conflicts. So, when learning foreign languages, the enrichment of foreign students’ individual experience of communication with another linguistic culture and the result of foreign language training are positive changes in the overall structure of students’ behavior. The author is convinced that the systematic, purposeful teachers’ work to overcome adaptation difficulties is the key to the successful adaptation of foreign students, the further development of each student as a person and future specialist. The better the Ukrainian (Russian) language is learned, the more adaptive it is, the more students adapt to the new socio-cultural environment, the better and more successful is the process of joining a new educational system and the sphere of interethnic communication with representatives of different countries. Prospects for further research are to find the forms and methods of work that will facilitate the acquisition of a foreign student to a new environment. The teacher must create certain conditions for foreigners to comprehend the linguistic material and learn to participate in the dialogue communication of the society in an active way.